Respuesta :

Given that xy=1. Now we have to use this equation to find the value of

[tex] \frac{2^{(x+y)^2}}{2^{(x-y)^2}} [/tex]

[tex] =2^{\left((x+y)^2-(x-y)^2\right)} [/tex]

[tex] =2^{\left(x^2+y^2+2xy-(x^2+y^2-2xy)\right)}[/tex]

[tex] =2^{\left(x^2+y^2+2xy-x^2-y^2+2xy\right)} [/tex]

[tex] =2^{\left(2xy+2xy\right)}[/tex]

[tex] =2^{\left(4xy\right)}[/tex]

[tex] =2^{\left(4xy\right)}[/tex]

Now plug the given value of xy=1

[tex] =2^{4*1}[/tex]

[tex] =2^{4}[/tex]

[tex] =16[/tex]

Hence final answer is 16.

ACCESS MORE